Research report : cognitive aspects of step-terms in american kinship. - Widmer, Eric (American Antropological Association, 1999)
In this article we extend the study of judged similarity among kinship terms from consanguineal to stepterms. Based on a sample of college students, we present a Euclidean representation of American kinship terms that shows that the distinction between consanguineal terms and step- terms is crucial. This representation matches predictions from the componential analysis paradigm and is shared by respondents of both genders with different ethnicities and first languages spoken.